EPE type three-layer co-extrusion adhesive film as well as preparation method and application thereof

By using EPE-type three-layer coextruded film in the packaging structure of single glass module of solar cell, combined with anti-PID additives and hydrolysis additives, the problem of insufficient anti-PID and corrosion resistance of the components under high temperature and high humidity conditions is solved, and excellent anti-PID and anti-aging performance is achieved, ensuring the long-term stability of the components and high power generation efficiency.

CN119752345AActive Publication Date: 2025-04-04CYBRID TECHNOLOGIES INC

Patent Information

Application Number
CN202411989113.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-04
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

Existing solar cell single glass modules have problems with insufficient PID performance and corrosion resistance under high temperature and high humidity conditions, resulting in poor long-term aging resistance, affecting the stability and life of the module.

Method used

An EPE type three-layer coextruded adhesive film is adopted, including a first transparent EVA outer layer, a transparent POE intermediate layer and a second transparent EVA outer layer arranged in sequence from top to bottom, and an anti-PID additive and a hydrolysis-resistant additive are added respectively to improve anti-PID performance and hydrolysis-resistant performance.

Benefits of technology

It significantly improves the PID and DH aging performance of the solar cell module package structure, reduces the power attenuation of PID and DH aging, and ensures the long-term stability of the module under high temperature and high humidity conditions and high power generation efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005223244680000131
    Figure BDA0005223244680000131
  • Figure BDA0005223244680000141
    Figure BDA0005223244680000141
Patent Text Reader

Abstract

The invention relates to an EPE type three-layer co-extrusion adhesive film as well as a preparation method and application thereof. The EPE type three-layer co-extrusion adhesive film comprises a first transparent EVA outer layer, a transparent POE middle layer and a second transparent EVA outer layer which are sequentially arranged from top to bottom, the first transparent EVA outer layer and the second transparent EVA outer layer are prepared from an EVA resin composition, and the EVA resin composition comprises the following components: EVA resin, an anti-PID auxiliary agent, a first main cross-linking agent and a second auxiliary cross-linking agent; the transparent POE middle layer is prepared from a POE resin composition, and the POE resin composition comprises the following components: POE resin, a hydrolysis-resistant auxiliary agent, a first main cross-linking agent and a second auxiliary cross-linking agent. According to the EPE type three-layer co-extrusion adhesive film provided by the invention, the preparation method is simple, and the PID resistance and long-term aging resistance of a TOPCON battery photovoltaic single-glass assembly are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of adhesive film packaging materials, and in particular to an EPE type three-layer co-extruded adhesive film and a preparation method and application thereof. Background Art

[0002] The packaging materials of solar cell modules are bonded to the photovoltaic glass and back panel to prevent water vapor intrusion and corrosion of the cells, which can provide protection for solar cell modules and improve the long-term stability of solar cell modules. At present, the packaging of solar cell single glass modules on the market is mainly used in distributed roofs, ground photovoltaic power stations and outdoor photovoltaic applications. However, under high temperature and high humidity conditions, there are problems such as the grid lines of the cells are easily corroded by water vapor and the long-term aging resistance is poor, resulting in a low market share of TOPCON single glass cells and cannot be widely used.

[0003] Based on the requirements of lightweight components for distributed roofs, many double-glass TOPCON components cannot meet the load-bearing requirements of distributed roofs. If the backplane of the single-glass packaging method is changed to a water-blocking aluminum backplane, although it has good water blocking, there are certain problems with the edge insulation, which is prone to leakage current. Other super-water-blocking backplanes have good water blocking, but the cost is relatively high. At present, the DH2000h power attenuation of conventional EPE single-glass packaging materials is greater than 5%, which cannot meet the requirements of photovoltaic modules for long-term aging performance. The DH2000h power attenuation of conventional POE single-glass packaging materials is less than 5%. Although it can meet the requirements for long-term aging performance, the POE packaging cost is relatively high, and there are problems such as slippage with the battery cell and low lamination efficiency.

[0004] CN118222200A provides a multilayer adhesive film for photovoltaic module encapsulation, which mainly includes an EVA layer and a POE layer with an auxiliary agent inside, and a barrier layer tightly combined between the EVA layer and the POE layer. Among them, the barrier layer is added with a photoinitiator, a pre-crosslinking process is used to provide a certain degree of crosslinking, and the POE layer is added with an inorganic micropowder adsorption auxiliary agent containing a plurality of holes to prevent the auxiliary agent in the POE from migrating to the EVA layer, and has better water-blocking performance and stable performance. However, this solution cannot effectively solve the PID phenomenon that occurs in solar cell modules under high temperature and high humidity conditions, and the barrier layer may turn yellow using a light-induced irradiation process, and increases the complexity of the operation.

[0005] CN110041835A provides a multi-layer co-extruded anti-polarization composite adhesive film and a preparation method thereof, which adopts a laminated structure of an upper POE layer, an anti-polarization layer and a lower EVA layer. The anti-polarization layer is an acrylic copolymer containing an ethylene chain segment. The prepared adhesive film has good compatibility with EVA and POE, has certain barrier properties, can effectively solve the PID phenomenon that occurs in solar cell modules under high-pressure, humid and hot environments, and has good bonding properties with glass substrates and back panels, thereby increasing the life of the modules. However, it will reduce light transmittance and affect normal power generation efficiency. The anti-PID and anti-corrosion properties of the encapsulation adhesive film provided by it need to be further improved.

[0006] Therefore, the existing technology has the defects of insufficient anti-PID performance and anti-corrosion performance of single-glass components. Therefore, how to improve the anti-PID performance and DH aging performance of single-glass components while ensuring the basic performance of single-glass components has become a problem that needs to be solved urgently. Summary of the invention

[0007] In order to solve the above technical problems, the present invention provides an EPE type three-layer co-extruded film and a preparation method and application thereof. The EPE type three-layer co-extruded film not only has excellent anti-PID performance and anti-DH aging performance, but also has high power generation efficiency.

[0008] To achieve this object, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides an EPE type three-layer co-extruded adhesive film, wherein the EPE type three-layer co-extruded adhesive film comprises a first transparent EVA outer layer, a transparent POE middle layer and a second transparent EVA outer layer arranged in sequence from top to bottom.

[0010] The raw materials for preparing the first transparent EVA outer layer and the second transparent EVA outer layer include an EVA resin composition, and the EVA resin composition includes the following components: EVA resin, an anti-PID auxiliary agent, a first main cross-linking agent and a second auxiliary cross-linking agent.

[0011] The raw material for preparing the transparent POE intermediate layer includes a POE resin composition, and the POE resin composition includes the following components: a POE resin, an anti-hydrolysis auxiliary agent, a first main cross-linking agent, and a second auxiliary cross-linking agent.

[0012] The EPE type three-layer co-extruded film provided by the present invention comprises a first transparent EVA outer layer, a second transparent EVA outer layer and a transparent POE middle layer. The transparent POE middle layer contains a hydrolysis-resistant additive, which inhibits the decomposition of the polymer, so that the prepared solar cell module packaging structure has excellent anti-yellowing and hydrolysis resistance effects, and the transparent EVA outer layer contains an anti-PID additive, which can dissipate the charge enriched on the battery surface, thereby improving the anti-PID performance of the solar cell module packaging structure.

[0013] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.

[0014] Preferably, the anti-PID additive includes any one of modified SEBS resin, polymethyl methacrylate, epoxy acrylate or ethylene-methyl methacrylate resin, or a combination of at least two thereof.

[0015] Preferably, the softening temperature of the anti-PID additive is 60-100°C, for example, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C or 100°C.

[0016] Preferably, the anti-hydrolysis aid includes any one of alicyclic polycarbodiimide, aliphatic polycarbodiimide or aromatic polycarbodiimide, or a combination of at least two thereof, and more preferably alicyclic polycarbodiimide.

[0017] Preferably, the melting temperature of the anti-hydrolysis aid is 70-90°C, for example, 70°C, 75°C, 80°C, 82°C, 85°C or 90°C.

[0018] Preferably, the EVA resin composition comprises the following components in parts by weight: 90 to 100 parts by weight of EVA resin (for example, 90 parts by weight, 92 parts by weight, 94 parts by weight, 96 parts by weight, 98 parts by weight or 100 parts by weight, etc.), 1 to 10 parts by weight of anti-PID additive (for example, 1.0 parts by weight, 2.0 parts by weight, 3.0 parts by weight, 4.0 parts by weight, 5.0 parts by weight, 6.0 parts by weight, 7.0 parts by weight, 8.0 parts by weight, 9.0 parts by weight or 10.0 parts by weight, etc.), 0.5 to 1 part by weight of a first main cross-linking agent (for example, 0.5 parts by weight, 0.6 parts by weight, 0.7 parts by weight, 0.8 parts by weight, 0.9 parts by weight or 1.0 parts by weight, etc.), and 0.5 to 1.5 parts by weight of a second auxiliary cross-linking agent (for example, 0.5 parts by weight, 0.7 parts by weight, 0.8 parts by weight, 1.0 parts by weight, 1.2 parts by weight or 1.5 parts by weight, etc.).

[0019] Preferably, the POE resin composition comprises the following components in parts by weight: 92 to 100 parts by weight of POE resin (for example, 92 parts by weight, 94 parts by weight, 96 parts by weight, 98 parts by weight or 100 parts by weight, etc.), 0.2 to 2 parts by weight of an anti-hydrolysis aid (for example, 0.2 parts by weight, 0.4 parts by weight, 0.6 parts by weight, 0.8 parts by weight, 1 parts by weight, 1.2 parts by weight, 1.4 parts by weight, 1.6 parts by weight, 1.8 parts by weight or 2.0 parts by weight, etc.), 0.5 to 1.5 parts by weight of a first main cross-linking agent (for example, 0.5 parts by weight, 0.6 parts by weight, 0.7 parts by weight, 0.9 parts by weight, 1.2 parts by weight or 1.5 parts by weight, etc.), and 0.5 to 2.0 parts by weight of a second auxiliary cross-linking agent (for example, 0.5 parts by weight, for example, 0.8 parts by weight, 1.0 parts by weight, 1.2 parts by weight, 1.5 parts by weight, 1.8 parts by weight or 2.0 parts by weight, etc.).

[0020] Preferably, the POE resin composition and the EVA resin composition both further include a coupling agent and / or a light stabilizer.

[0021] Preferably, the content of the coupling agent in the EVA resin composition is 0.1 to 1.0 part by weight, for example, 0.1 part by weight, 0.2 part by weight, 0.4 part by weight, 0.6 part by weight, 0.8 part by weight or 1.0 part by weight.

[0022] Preferably, the content of the light stabilizer in the EVA resin composition is 0.1 to 0.5 parts by weight, for example, 0.1 parts by weight, 0.2 parts by weight, 0.3 parts by weight, 0.4 parts by weight or 0.5 parts by weight.

[0023] Preferably, the content of the coupling agent in the POE resin composition is 0.1 to 1.0 parts by weight, for example, 0.1 parts by weight, 0.2 parts by weight, 0.4 parts by weight, 0.6 parts by weight, 0.8 parts by weight or 1.0 parts by weight.

[0024] Preferably, the content of the light stabilizer in the POE resin composition is 0.1 to 0.5 parts by weight, for example, 0.1 parts by weight, 0.2 parts by weight, 0.3 parts by weight, 0.4 parts by weight or 0.5 parts by weight.

[0025] Preferably, the coupling agent includes vinyltrimethoxysilane, vinyltriethoxysilane, N-aminoethyl-3-aminopropylmethyldimethoxysilane, 3-(methacryloxypropyl)trimethoxysilane or vinyltri(2-methoxyethoxy)silane, or any one thereof or a combination of at least two thereof.

[0026] Preferably, the light stabilizer includes any one of light stabilizer 123, light stabilizer 292, light stabilizer 770, light stabilizer 944 or light stabilizer 2020, or a combination of at least two of them, and light stabilizer 292 is more preferred.

[0027] Preferably, the first primary cross-linking agent comprises an organic peroxide initiator.

[0028] Preferably, the organic peroxide initiator comprises any one of dicyclohexyl peroxydicarbonate, tert-butyl peroxyisobutyrate, tert-butyl peroxyacetate, diisopropyl peroxydicarbonate, tert-butyl peroxy-2-ethylhexyl carbonate, tert-pentyl peroxycarbonate-2-ethylhexanoate or tert-hexyl peroxycarbonate-2-ethylhexanoate, or a combination of at least two thereof.

[0029] Preferably, the second auxiliary crosslinking agent includes any one of triallyl isocyanurate, methyl trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, pentaerythritol tetraacrylate, tricyclodecane dimethanol diacrylate, tripropylene glycol diacrylate or 1,6-hexanediol diacrylate, or a combination of at least two thereof.

[0030] Preferably, the EVA resin composition further comprises an acid absorbent.

[0031] Preferably, the content of the acid scavenger in the EVA resin composition is 0.01 to 0.15 parts by weight, for example, 0.01 parts by weight, 0.03 parts by weight, 0.05 parts by weight, 0.1 parts by weight, 0.13 parts by weight or 0.15 parts by weight.

[0032] Preferably, the acid absorbent includes any one of magnesium hydroxide, magnesium oxide, calcium hydroxide, aluminum hydroxide, calcium carbonate or magnesium aluminum hydrotalcite, or a combination of at least two thereof.

[0033] Preferably, the thickness of the first transparent EVA outer layer and the second transparent EVA outer layer are independently 150-200 μm, for example, 150 μm, 160 μm, 170 μm, 180 μm, 190 μm or 200 μm.

[0034] Preferably, the thickness of the transparent POE intermediate layer is 50-180 μm, for example, 50 μm, 60 μm, 80 μm, 100 μm, 110 μm, 130 μm, 150 μm or 180 μm.

[0035] Preferably, the melt index of the EVA resin and the POE resin are both 6 to 20 g / 10 min, for example, 6 g / 10 min, 8 g / 10 min, 12 g / 10 min, 15 g / 10 min, 18 g / 10 min or 20 g / 10 min.

[0036] Preferably, the transmittance of the EVA resin and the POE resin are both greater than 82%, for example, may be 84%, 85%, 86%, 87%, 88%, 89%, 90% or 92%.

[0037] Preferably, the volume resistivity of the EVA resin is ≥1×10 15 Ω·cm, for example, can be 1.5×10 15 Ω·cm、1.8×10 15 Ω·cm、2.5×10 15 Ω·cm、3.2×10 15 Ω·cm or 4.0×10 15 Ω·cm, etc.

[0038] Preferably, the volume resistivity of the POE resin is ≥1×10 16 Ω·cm, for example, can be 1.5×10 16 Ω·cm、2.0×10 16 Ω·cm、3.0×10 16 Ω·cm、4.0×10 16 Ω·cm or 5.0×10 16 Ω·cm, etc.

[0039] In a second aspect, the present invention provides a method for preparing an EPE three-layer co-extruded film as described in the first aspect, the preparation method comprising the following steps: respectively putting the raw materials for preparing a first transparent EVA outer layer, the raw materials for preparing a transparent POE middle layer, and the raw materials for preparing a second transparent EVA outer layer into respective barrels, and then hot-melt extruding, stretching, pulling, and winding to form an EPE three-layer co-extruded film having a first transparent EVA outer layer, a transparent POE middle layer, and a second transparent EVA outer layer arranged in sequence from top to bottom.

[0040] Preferably, the temperature of the hot melt extrusion is 80-110°C, for example, it may be 80°C, 82°C, 84°C, 88°C, 90°C, 92°C, 94°C, 98°C, 100°C, 102°C, 104°C, 108°C or 110°C, etc.

[0041] In a third aspect, the present invention provides an EPE type three-layer co-extruded adhesive film as described in the first aspect for use in a laser sintering process TOPCON cell photovoltaic single glass component.

[0042] Compared with the prior art, the present invention has at least the following beneficial effects:

[0043] (1) The EPE type three-layer co-extruded film provided by the present invention has an anti-PID additive and a hydrolysis-resistant additive added to the transparent EVA outer layer and the transparent POE middle layer, respectively, and both additives have good compatibility with the resin. While not affecting the high transmittance, fluidity, strength and heat resistance of the system, the volume resistivity and hydrolysis resistance are further improved. Under high temperature and high humidity conditions, the PID and DH aging power attenuation of the product are significantly reduced by the coordinated use of the anti-PID additive and the hydrolysis-resistant additive.

[0044] (2) The EPE three-layer co-extruded film provided by the present invention has qualified light transmittance after cross-linking ((380-1100nm)>90%), qualified yellowing value (<3%), qualified PID192h (<4%), and qualified DH2000h (<4%).

[0045] (3) The preferred technical solution of the present invention uses alicyclic polycarbodiimide as a hydrolysis resistance additive. Compared with other hydrolysis resistance additives, the alicyclic polycarbodiimide is used in combination with an anti-PID additive to produce a product with better hydrolysis resistance. DETAILED DESCRIPTION

[0046] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0047] The sources of raw materials used in the following examples and comparative examples are as follows:

[0048] 1. EVA resin: EVA20F20, purchased from Yanshan Petrochemical, with a melt index of 20g / 10min and a VA content of 20%;

[0049] 2. POE resin: LF675, purchased from LG Chemical;

[0050] 3. Modified SEBS resin: MD-6932M, purchased from Kraton, USA;

[0051] 4. Ethylene-methyl methacrylate resin: WK402, purchased from Sumitomo, Japan;

[0052] 5. Polymethyl methacrylate: LP3104, purchased from Mitsubishi Rayon, Japan;

[0053] 6. Epoxy acrylate: GA-480, purchased from Akzo Nobel;

[0054] 7. Alicyclic polycarbodiimide: BIO-372, purchased from Jiangsu Keshengtong New Materials;

[0055] 8. Aromatic polycarbodiimide: HM220, purchased from Shanghai Langyi New Materials.

[0056] Example 1

[0057] An EPE type three-layer co-extruded film consists of a first transparent EVA outer layer, a transparent POE middle layer and a second transparent EVA outer layer from top to bottom.

[0058] The first transparent EVA outer layer and the second transparent EVA outer layer are made of EVA resin composition, and both have a thickness of 180 μm.

[0059] The EVA resin composition includes the following components: 95.0 parts by weight of EVA resin, 5.0 parts by weight of modified SEBS resin, 0.5 parts by weight of 2-ethylhexanoic acid triamyl peroxycarbonate, 0.3 parts by weight of triallyl isocyanurate, 0.5 parts by weight of propoxylated trimethylolpropane triacrylate, 0.2 parts by weight of vinyl tri(2-methoxyethoxy) silane, 0.2 parts by weight of light stabilizer 292 and 0.1 parts by weight of acid absorbent magnesium aluminum hydrotalcite.

[0060] The raw material for preparing the transparent POE intermediate layer is a POE resin composition, and the thickness is 100 μm.

[0061] The POE resin composition includes the following components: 99.5 parts by weight of POE resin, 0.8 parts by weight of alicyclic polycarbodiimide, 0.8 parts by weight of tert-hexyl peroxycarbonate-2-ethylhexanoate, 0.85 parts by weight of triallyl isocyanurate, 0.2 parts by weight of 1,6-hexanediol diacrylate, 0.3 parts by weight of 3-(methacryloxypropyl)trimethoxysilane and 0.2 parts by weight of light stabilizer 292.

[0062] The preparation method of the EPE type three-layer co-extruded film comprises: respectively putting an EVA resin composition, a POE resin composition and an EVA resin composition into respective barrels, and then hot-melt extruding, stretching, pulling and winding to form the EPE type three-layer co-extruded film.

[0063] The temperature of the hot melt extrusion is 95°C.

[0064] Example 2

[0065] An EPE type three-layer co-extruded film consists of a first transparent EVA outer layer, a transparent POE middle layer and a second transparent EVA outer layer from top to bottom.

[0066] The raw materials for preparing the first transparent EVA outer layer and the second transparent EVA outer layer are EVA resin compositions, and the thickness of both layers is 200 μm.

[0067] The EVA resin composition includes the following components: 90.0 parts by weight of EVA resin, 2.0 parts by weight of ethylene-methyl methacrylate resin, 0.7 parts by weight of dicyclohexyl peroxydicarbonate, 0.2 parts by weight of methyl trimethylolpropane triacrylate, 0.3 parts by weight of pentaerythritol tetraacrylate, 0.5 parts by weight of N-aminoethyl-3-aminopropylmethyldimethoxysilane, 0.5 parts by weight of light stabilizer 123 and 0.1 parts by weight of acid absorber magnesium hydroxide.

[0068] The raw material for preparing the transparent POE intermediate layer is a POE resin composition, and the thickness is 180 μm.

[0069] The POE resin composition includes the following components: 92 parts by weight of POE resin, 0.2 parts by weight of alicyclic polycarbodiimide, 0.5 parts by weight of diisopropyl peroxydicarbonate, 0.4 parts by weight of methyl trimethylolpropane triacrylate, 0.3 parts by weight of tricyclodecane dimethanol diacrylate, 0.3 parts by weight of vinyl trimethoxy silane and 0.2 parts by weight of light stabilizer 123.

[0070] The preparation method of the EPE type three-layer co-extruded film comprises: respectively putting an EVA resin composition, a POE resin composition and an EVA resin composition into respective barrels, and then hot-melt extruding at 80° C., stretching, pulling and winding to form the EPE type three-layer co-extruded film.

[0071] The temperature of the hot melt extrusion is 80°C.

[0072] Example 3

[0073] An EPE type three-layer co-extruded film consists of a first transparent EVA outer layer, a transparent POE middle layer and a second transparent EVA outer layer from top to bottom.

[0074] The raw materials for preparing the first transparent EVA outer layer and the second transparent EVA outer layer are EVA resin compositions, and the thickness of both layers is 150 μm.

[0075] The EVA resin composition includes the following components: 98.0 parts by weight of EVA resin, 8.0 parts by weight of polymethyl methacrylate, 0.8 parts by weight of tert-butyl peroxyisobutyrate, 0.6 parts by weight of triallyl isocyanurate, 0.7 parts by weight of propoxylated trimethylolpropane triacrylate, 0.8 parts by weight of vinyl triethoxysilane, 0.1 parts by weight of light stabilizer 770 and 0.15 parts by weight of acid absorber calcium carbonate.

[0076] The raw material for preparing the transparent POE intermediate layer is a POE resin composition, and the thickness is 50 μm.

[0077] The POE resin composition includes the following components: 95 parts by weight of POE resin, 1.5 parts by weight of alicyclic polycarbodiimide, 1.0 parts by weight of tert-butyl peroxyacetate, 0.8 parts by weight of triallyl isocyanurate, 0.6 parts by weight of tripropylene glycol diacrylate, 1.0 parts by weight of vinyl triethoxysilane and 0.1 parts by weight of light stabilizer 770.

[0078] The preparation method of the EPE type three-layer co-extruded film comprises: respectively putting an EVA resin composition, a POE resin composition and an EVA resin composition into respective barrels, and then hot-melt extruding at 110° C., stretching, pulling and winding to form the EPE type three-layer co-extruded film.

[0079] The temperature of the hot melt extrusion is 110°C.

[0080] Example 4

[0081] An EPE type three-layer co-extruded film, which differs from Example 1 in that the anti-PID auxiliary agent of the transparent EVA outer layer is epoxy acrylate.

[0082] Example 5

[0083] An EPE type three-layer co-extruded film is different from Example 1 in that the anti-PID additive of the EVA outer layer is a combination of 3.0 parts by weight of modified SEBS resin and 2.0 parts by weight of polymethyl methacrylate resin.

[0084] Example 6

[0085] An EPE type three-layer co-extruded film is different from Example 1 in that the anti-PID additive of the transparent EVA outer layer is a combination of 3.0 parts by weight of modified SEBS resin and 2.0 parts by weight of epoxy acrylate.

[0086] Example 7

[0087] An EPE type three-layer co-extruded film is different from Example 1 in that the anti-PID additive of the transparent EVA outer layer is a combination of 3.0 parts by weight of ethylene-methyl methacrylate and 2.0 parts by weight of polymethyl methacrylate resin.

[0088] Example 8

[0089] An EPE type three-layer co-extruded film is different from Example 1 in that the anti-PID additive of the transparent EVA outer layer is a combination of 3.0 parts by weight of ethylene-methyl methacrylate and 2.0 parts by weight of epoxy acrylate.

[0090] Example 9

[0091] An EPE type three-layer co-extruded film, which differs from Example 1 in that the anti-hydrolysis additive of the transparent POE middle layer is aromatic polycarbodiimide.

[0092] Comparative Example 1

[0093] An EPE type three-layer co-extruded film, which is different from Example 1 in that the transparent EVA outer layer does not contain an anti-PID additive, and the transparent POE middle layer does not contain an anti-hydrolysis additive.

[0094] Comparative Example 2

[0095] An EPE type three-layer co-extruded film, which differs from Example 1 in that the transparent POE intermediate layer does not contain an anti-hydrolysis additive.

[0096] Comparative Example 3

[0097] An EPE type three-layer co-extruded film is different from Example 1 in that the anti-PID additive of the transparent EVA outer layer is 5.0 parts by weight of ethylene-methyl methacrylate, and the transparent POE middle layer does not contain an anti-hydrolysis additive.

[0098] Comparative Example 4

[0099] An EPE type three-layer co-extruded film, which differs from Example 1 in that the transparent EVA outer layer does not contain an anti-PID additive.

[0100] Comparative Example 5

[0101] An EPE type three-layer co-extruded film is different from Example 1 in that the transparent EVA outer layer contains 0.8 parts by weight of alicyclic polycarbodiimide, an anti-hydrolysis aid, and the transparent POE middle layer does not contain an anti-hydrolysis aid.

[0102] Comparative Example 6

[0103] An EPE type three-layer co-extruded film, which differs from Example 1 in that the anti-hydrolysis additive of the transparent POE middle layer is a monomeric carbodiimide.

[0104] Test Method

[0105] Preparation of white EVA film for back side film:

[0106] The back adhesive film white EVA film is mainly an EVA resin composition, which consists of the following components in parts by weight: 100 parts by weight of EVA resin, 0.8 parts by weight of titanium dioxide, 0.5 parts by weight of t-pentyl peroxycarbonate-2-ethylhexanoate, 0.3 parts by weight of triallyl isocyanurate, 0.5 parts by weight of propoxylated trimethylolpropane triacrylate, 0.2 parts by weight of vinyl tri(2-methoxyethoxy) silane, 0.2 parts by weight of light stabilizer 292 and 0.1 parts by weight of acid absorber magnesium aluminum hydrotalcite.

[0107] The EPE encapsulation film and the white EVA film provided in the embodiment and the comparative example are respectively assembled into a single glass component, and the method is as follows:

[0108] Solar cell module packaging structure: glass + EPE film + Jietai LECO-TOPCON battery cell + white EVA film + white KPF backplane, where the glass is 2mm rolled process glass; the thickness of the EPE film is 450μm, the transparent EVA layer is 180μm, and the transparent POE middle layer is 90μm; the thickness of the white EVA film is 380μm; the battery cell is 182*72 standard Jietai LECO-TOPCON battery cell with a thickness of about 130μm.

[0109] The above structure was tested after lamination, and the lamination conditions were: 145° C., vacuum time 5 min, and lamination time 10 min.

[0110] Test Standards

[0111] (1) Light transmittance: Tested in accordance with GB / T 29848-2018;

[0112] (2) UV+DH test: The test was carried out according to the test method provided in IEC 61215-2:2016. The UV+DH test temperature was 85°C, the relative humidity was 85%, and the irradiance was 150 kWh / m 2 ;

[0113] (3) Anti-PID performance test: refer to the standard "IEC 61215-2020", the experimental temperature is 85°C, the relative humidity is 85%, and the time is 192h;

[0114] (4) Resistance to humidity and heat aging: The test was conducted in accordance with the test method provided in IEC 61215-2:2016. The humidity and heat test temperature was 85°C, the relative humidity was 85%, and the time was 2000 h.

[0115] Test Results

[0116] The EPE three-layer co-extruded films provided in Examples 1-9 and Comparative Examples 1-6 were tested according to the above test method. The test results are shown in Table 1:

[0117] Table 1

[0118]

[0119]

[0120] The test results show that:

[0121] (1) It can be seen from Examples 1 to 8 that the present invention introduces anti-PID additives and anti-hydrolysis additives to make the transmittance of the solar cell module packaging structure meet the requirement of >90%, without affecting its transmittance. When UV+DH is tested to 150KW, the yellowing value is <3%, and the PID192h and DH2000h results are both <3%.

[0122] (2) It can be seen from Example 9 that the solar cell module packaging structure prepared by adding aromatic polycarbodiimide as an anti-hydrolysis aid has a DH2000h of <4%, but will cause severe yellowing after UV150KW aging, with a yellowing value of >3%.

[0123] (3) Compared with Examples 1-8, no anti-PID additive and anti-hydrolysis agent are added to the raw materials for preparing the EPE film provided in Comparative Example 1. The transmittance of the obtained solar cell module packaging structure is greater than 90%, and the UV+DH test reaches 150KW. The yellowing value is less than 3%, but the PID192h and DH2000h are both greater than 4%, which does not meet the requirements.

[0124] (4) Compared with Example 1, the EPE film provided in Comparative Example 2 is prepared by adding an anti-PID additive to modify the SEBS resin, without adding an anti-hydrolysis agent. The resulting solar cell module packaging structure has a transmittance of >90%, a UV+DH test of 150KW, and a yellowing value of <3%, but PID192h is qualified and DH2000h>4% is unqualified.

[0125] (5) Compared with Examples 1-2, the EPE film provided in Comparative Example 3 is prepared by adding an anti-PID additive to modify the SEBS resin in the raw materials, without adding an anti-hydrolysis agent, and the transmittance is greater than 90%, the UV+DH test reaches 150KW, the yellowing value is less than 3%, the PID192h is qualified, and the DH2000h>4% is unqualified.

[0126] (6) Compared with Example 1, the EPE film provided in Comparative Example 4 does not add an anti-PID additive to the raw materials for preparing the EPE film, but only adds an anti-hydrolysis agent. The transmittance is slightly reduced, but the transmittance requirement of >90% is met; the UV+DH test reaches 150KW, and the yellowing value is slightly increased, but meets the requirement of <3%, PID192h>4% is unqualified, and DH2000h is qualified.

[0127] (7) Compared with Example 1, the raw materials for preparing the EPE film provided in Comparative Example 5 contain 0.8 parts by weight of alicyclic polycarbodiimide as an anti-hydrolysis aid in the transparent EVA outer layer, and the transparent POE middle layer does not contain an anti-hydrolysis aid. When the transparent EVA outer layer contains both an anti-hydrolysis aid and an anti-PID aid, its anti-PID performance will be affected. PID192h>4% is unqualified, and DH2000h is qualified.

[0128] (8) Compared with Example 1, the anti-hydrolysis aid in the preparation raw material of the EPE film provided in Comparative Example 6 is replaced with a monomeric carbodiimide, and the DH2000h of the obtained solar cell module packaging structure is greater than 4%, which does not meet the requirements.

[0129] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. An EPE type three-layer co-extruded film, characterized in that: The EPE type three-layer co-extruded film comprises a first transparent EVA outer layer, a transparent POE middle layer and a second transparent EVA outer layer arranged in sequence from top to bottom; The raw materials for preparing the first transparent EVA outer layer and the second transparent EVA outer layer include an EVA resin composition, and the EVA resin composition includes the following components: EVA resin, an anti-PID auxiliary agent, a first main cross-linking agent and a second auxiliary cross-linking agent; The raw material for preparing the transparent POE intermediate layer includes a POE resin composition, and the POE resin composition includes the following components: a POE resin, an anti-hydrolysis auxiliary agent, a first main cross-linking agent, and a second auxiliary cross-linking agent.

2. The EPE three-layer co-extruded film according to claim 1, characterized in that: The anti-PID additive includes any one or a combination of at least two of modified SEBS resin, polymethyl methacrylate, epoxy acrylate or ethylene-methyl methacrylate resin; Preferably, the anti-hydrolysis aid includes any one of alicyclic polycarbodiimide, aliphatic polycarbodiimide or aromatic polycarbodiimide, or a combination of at least two thereof, and more preferably alicyclic polycarbodiimide.

3. The EPE three-layer co-extruded film according to claim 1 or 2, characterized in that: The EVA resin composition comprises the following components in parts by weight: 90 to 100 parts by weight of EVA resin, 1 to 10 parts by weight of an anti-PID additive, 0.5 to 1 part by weight of a first primary cross-linking agent, and 0.5 to 1.5 parts by weight of a second auxiliary cross-linking agent; Preferably, the POE resin composition comprises the following components in parts by weight: 92 to 100 parts by weight of POE resin, 0.2 to 2 parts by weight of an anti-hydrolysis aid, 0.5 to 1.5 parts by weight of a first primary cross-linking agent, and 0.5 to 2.0 parts by weight of a second auxiliary cross-linking agent; Preferably, the POE resin composition and the EVA resin composition both further include a coupling agent and / or a light stabilizer; Preferably, the content of the coupling agent in the EVA resin composition is 0.1 to 1.0 parts by weight; Preferably, the content of the light stabilizer in the EVA resin composition is 0.1 to 0.5 parts by weight; Preferably, the content of the coupling agent in the POE resin composition is 0.1 to 1.0 parts by weight; Preferably, the content of the light stabilizer in the POE resin composition is 0.1 to 0.5 parts by weight; Preferably, the coupling agent comprises vinyltrimethoxysilane, vinyltriethoxysilane, N-aminoethyl-3-aminopropylmethyldimethoxysilane, 3-(methacryloxypropyl)trimethoxysilane or vinyltri(2-methoxyethoxy)silane or any one thereof or a combination of at least two thereof; Preferably, the light stabilizer includes any one of light stabilizer 123, light stabilizer 292, light stabilizer 770, light stabilizer 944 or light stabilizer 2020, or a combination of at least two of them, and light stabilizer 292 is more preferred.

4. The EPE three-layer co-extruded film according to any one of claims 1 to 3, characterized in that: The first primary cross-linking agent includes an organic peroxide initiator; Preferably, the organic peroxide initiator comprises any one of dicyclohexyl peroxydicarbonate, tert-butyl peroxyisobutyrate, tert-butyl peroxyacetate, diisopropyl peroxydicarbonate, tert-butyl peroxy-2-ethylhexyl carbonate, tert-pentyl peroxycarbonate-2-ethylhexanoate or tert-hexyl peroxycarbonate-2-ethylhexanoate, or a combination of at least two thereof.

5. The EPE three-layer co-extruded film according to any one of claims 1 to 4, characterized in that: The second auxiliary crosslinking agent includes any one of triallyl isocyanurate, methyl trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, pentaerythritol tetraacrylate, tricyclodecane dimethanol diacrylate, tripropylene glycol diacrylate or 1,6-hexanediol diacrylate, or a combination of at least two thereof.

6. The EPE three-layer co-extruded film according to any one of claims 1 to 5, characterized in that: The EVA resin composition also includes an acid absorbent; Preferably, the content of the acid scavenger in the EVA resin composition is 0.01 to 0.15 parts by weight; Preferably, the acid absorbent includes any one of magnesium hydroxide, magnesium oxide, calcium hydroxide, aluminum hydroxide, calcium carbonate or magnesium aluminum hydrotalcite, or a combination of at least two thereof.

7. The EPE three-layer co-extruded film according to any one of claims 1 to 6, characterized in that: The thickness of the first transparent EVA outer layer and the second transparent EVA outer layer are independently 150 to 200 μm; Preferably, the transparent POE intermediate layer has a thickness of 50 to 180 μm.

8. The EPE three-layer co-extruded film according to any one of claims 1 to 7, characterized in that: The melt index of the EVA resin and the POE resin is independently 6 to 20 g / 10 min; Preferably, the light transmittance of the EVA resin and the POE resin is both greater than 82%; Preferably, the volume resistivity of the EVA resin is ≥1×10 15 Ω·cm; Preferably, the volume resistivity of the POE resin is ≥1×10 16 Ω·cm.

9. A method for preparing an EPE type three-layer co-extruded film according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: putting the raw materials for preparing the first transparent EVA outer layer, the raw materials for preparing the transparent POE middle layer, and the raw materials for preparing the second transparent EVA outer layer into respective barrels, and then hot-melt extruding, stretching, pulling, and rolling to form an EPE type three-layer co-extruded film having the first transparent EVA outer layer, the transparent POE middle layer, and the second transparent EVA outer layer arranged in sequence from top to bottom; Preferably, the temperature of the hot melt extrusion is 80-110°C.

10. Application of the EPE type three-layer co-extruded adhesive film as claimed in any one of claims 1 to 8 in a laser sintering process TOPCON cell photovoltaic single glass module.

Citation Information

Patent Citations

  • Multilayer coextruded anti-polarization composite adhesive film and preparation method thereof

    CN110041835A

  • Multi-layer adhesive film for packaging photovoltaic module

    CN118222200A

  • Photovoltaic EVA film resisting PID

    CN103525321A

  • Double-sided battery grid backboard glass assembly and preparation method thereof

    CN113675286A

  • EPE photovoltaic adhesive film, preparation method thereof and photovoltaic module

    CN114774023A

Cited By

  • EPE photovoltaic adhesive film as well as preparation process and application thereof

    CN120484721A

  • Low-temperature-resistant multi-layer insulating blanket for hot-line work in alpine region and preparation method thereof

    CN120517029A

  • A low-temperature-resistant multi-layer insulation blanket for live working in high-altitude cold areas and its preparation method

    CN120517029B